Novel re duce d graphene oxide/zinc phthalocyanine and re duce d graphene oxide/cobalt phthalocyanine hybrids as high sensitivity room temperature volatile organic compound gas sensors - Yabas, Ebru; Bicer, Emre; Altindal, Ahmet (ELSEVIER, 2023)
In this work, novel 4-pyridynyl-oxadiazole tetrasubstituted zinc and cobalt phthalocyanine compounds were synthesized and characterized by UV-vis, Fluorescence spectroscopy, and SEM. Then these com-pounds were mixed with reduced graphene oxide. As a result of the interaction of these newly syn-thesized phthalocyanines with reduced graphene oxide (rGO), rGO/ZnPc and rGO/CoPc hybrids were ob-tained. The measurement results confirm that the prepared non-covalent rGO/ZnPc and rGO/CoPc hybrid structures are formed by strong pi-pi interaction. A comparative study of the sensor response of rGO and non-covalently functionalized with zinc and cobalt phthalocyanines (rGO/ZnPc, and rGO/CoPc) hybrids to five different volatile organic compound vapors, ammonia, acetone, ethanol, methanol and butanol is car-ried out. The response of the sensors increases with respect to ammonia concentrations ranging from 30 to 210 ppm. The response time for 120 ppm ammonia vapor were approximately 250s, 230s and 190s for rGO, rGO/ZnPc, and rGO/CoPc based sensors, respectively. Also, we have conducted selectivity exper-iments with the aformentioned vapors, thus, studies have indicated that functionalization of rGO with ZnPc results in a 43-fold improvement in sensor response towards ammonia vapors. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: Metallophthalocyanine; Graphene oxide; Hybrid; Gas sensor; Ammonia; NH3-SENSING PROPERTIES; BREATH ANALYSIS; COBALT; BIOMARKERS; OXADIAZOLE; MECHANISM; BEHAVIOR; ABILITY; Chemistry